2022
DOI: 10.1039/d1bm01848e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel adhesive formed via multiple chemical interactions: from persistent wet adhesion to rapid hemostasis

Abstract: Thus far, robust and durable adhesion capability of hydrogel adhesive in wet environment remains a huge challenge. Here, a chemically-physically double-network cross-linked hydrogel matrix was prepared by first mixing acrylic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
1
9
0
1
Order By: Relevance
“…In addition to self-healing properties, the abundant adhesion groups in the hydrogel network formed multiple interfacial bonds with the tissue surface, including electrostatic interactions and cation−π interactions in addition to hydrogen bond, resulting in strong adhesion (Figure H). To compare the variation of the adhesion strength of hydrogel sensors under physiological conditions upon exposure to various media, we tested the adhesion strength of GUT-PP hydrogels exposed to water, blood, grease, and air conditions by a lap shear test. The results in Figure S6 showed that the adhesion strength of GUT-PP hydrogels exposed to water and blood (∼10 kPa) decreased compared with that in air (∼16 kPa), due to the formation of a hydrated layer at the hydrogel–tissue interface, while the adhesive strength gap was further widened when the hydrogels were exposed to grease, which may be attributed to the self-lubricating effect of the grease.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to self-healing properties, the abundant adhesion groups in the hydrogel network formed multiple interfacial bonds with the tissue surface, including electrostatic interactions and cation−π interactions in addition to hydrogen bond, resulting in strong adhesion (Figure H). To compare the variation of the adhesion strength of hydrogel sensors under physiological conditions upon exposure to various media, we tested the adhesion strength of GUT-PP hydrogels exposed to water, blood, grease, and air conditions by a lap shear test. The results in Figure S6 showed that the adhesion strength of GUT-PP hydrogels exposed to water and blood (∼10 kPa) decreased compared with that in air (∼16 kPa), due to the formation of a hydrated layer at the hydrogel–tissue interface, while the adhesive strength gap was further widened when the hydrogels were exposed to grease, which may be attributed to the self-lubricating effect of the grease.…”
Section: Resultsmentioning
confidence: 99%
“…Liang et al used acrylic acid (AAc), CS, and TA to prepare low-swelling hydrogel Polymer-AAc/CS/TA (PAAc/CS/TA). 95 In this hydrogel, the CS chains entangled with each other and TA provided noncovalent interactions, which increased the cohesion and reduced the swelling rate of the hydrogel. Since Cl − and the N-glucosamine on the CS chain cannot attract each other in DIW, the swelling rate of hydrogel in DIW was slightly higher than that in PBS (Figure 7C).…”
Section: Anti-swelling Adhesive Hydrogelmentioning
confidence: 98%
“…Liang et al. used acrylic acid (AAc), CS, and TA to prepare low‐swelling hydrogel Polymer‐AAc/CS/TA (PAAc/CS/TA) 95 . In this hydrogel, the CS chains entangled with each other and TA provided non‐covalent interactions, which increased the cohesion and reduced the swelling rate of the hydrogel.…”
Section: Engineering Multifunctional Adhesive Hydrogelmentioning
confidence: 99%
“…The obtained CS/TA/SF hydrogels showed less bleeding and shorter hemostasis time in various arterial and visceral bleeding models compared to previously reported materials (Figure 7a). Later in another study, Liang et al created a physicochemical double network cross-linked hydrogel (PCT) using acrylic acid, CS, and TA as the main components [97]. The hydrogels have many active sites on their surfaces, allowing fast, strong and repetitive adhesion to artificial solids and biological tissues (Figure 7b).…”
Section: Heartmentioning
confidence: 99%